Overall survival with neratinib after trastuzumab-based adjuvant therapy in HER2-positive breast cancer (ExteNET): A randomised, double-blind, placebo-controlled, phase 3 trial. (May 2023) - Holmes, Frankie A.; Moy, Beverly; Delaloge, Suzette; Chia, Stephen K.L.; Ejlertsen, Bent; Mansi, Janine; Iwata, Hiroji; Gnant, Michael; Buyse, Marc; Barrios, Carlos H.; Silovski, Tajana; Šeparović, Robert; et al.
Abstract: Background: ExteNET showed that neratinib, an irreversible pan-HER tyrosine kinase inhibitor, given for 1 year after trastuzumab-based therapy significantly improved invasive disease-free survival in women with early-stage HER2-positive breast cancer. We report the final analysis of overall survival in ExteNET. Methods: In this international, randomised, double-blind, placebo-controlled, phase 3 trial, women aged 18 years or older with stage 1–3c (amended to stage 2–3c) HER2-positive breast cancer who had completed neoadjuvant and adjuvant chemotherapy plus trastuzumab were eligible. Patients were randomly assigned to oral neratinib 240 mg/day or placebo for 1 year. Randomisation was stratified according to hormone receptor (HR) status (HR-positive vs. HR-negative), nodal status (0, 1–3 or 4+), and trastuzumab regimen (sequentially vs. concurrently with chemotherapy). Overall survival was analysed by intention to treat. ExteNET is registered (Clinicaltrials.gov: NCT00878709 ) and is complete. Results: Between July 9, 2009, and October 24, 2011, 2840 women received neratinib (n = 1420) or placebo (n = 1420). After a median follow-up of 8.1 (IQR, 7.0–8.8) years, 127 patients (8.9%) in the neratinib group and 137 patients (9.6%) in the placebo group in the intention-to-treat population had died. Eight-year overall survival rates were 90.1% (95% CI 88.3–91.6) with neratinib and 90.2% (95% CI 88.4–91.7) with placebo (stratified hazard ratio 0.95; 95% CI 0.75–1.21; p = 0.6914). Conclusions: Overall survival in the extended adjuvant setting was comparable for neratinib and placebo after a median follow-up of 8.1 years in women with early-stage HER2-positive breast cancer. Highlights: Neratinib improves iDFS after trastuzumab in early HER2+ breast cancer. We report the final analysis of overall survival from the phase 3 ExteNET trial. At 8 years' follow-up, OS in the ITT population was similar with neratinib vs placebo.